2018
DOI: 10.12928/telkomnika.v16i3.7751
|View full text |Cite
|
Sign up to set email alerts
|

Improving Sentiment Analysis of Short Informal Indonesian Product Reviews using Synonym Based Feature Expansion

Abstract: Sentiment analysis in short informal texts like product reviews is more challenging. Short texts are sparse, noisy, and lack of context information. Traditional text classification methods may not b e suitab le for analyzing sentiment of short texts given all those difficulties. A common approach to overcome these prob lems is to enrich the original texts with additional semantics to make it appear like a large document of text. Then, traditional classification methods can b e applied to it. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
(16 reference statements)
0
12
0
2
Order By: Relevance
“…In filtering, uninformative words are removed based on the existing stoplist by by Tala [14]. The last process in preprocessing is stemming or restoring every words to its root [15][16]. In this case, we use Sastrawi Stemmer.…”
Section: Methodsmentioning
confidence: 99%
“…In filtering, uninformative words are removed based on the existing stoplist by by Tala [14]. The last process in preprocessing is stemming or restoring every words to its root [15][16]. In this case, we use Sastrawi Stemmer.…”
Section: Methodsmentioning
confidence: 99%
“…Seperti penggunaan kata-kata baku yang ditambahkan dengan beberapa kata slang, atau penggunaan kata baku, kata slang, dan kata singkatan dalam sebuah konten teks. Dalam beberapa kasus, proses melakukan normalisasi teks tersebut dilakukan dengan cara mengganti kata yang tidak baku dengan kata yang baku, seperti kata 'bisaaaaa' menjadi 'bisa' [26].…”
Section: Karakteristik Konten Media Sosial Orang Indonesiaunclassified
“…One of the most popular techniques is using machine learning approach. In recent years, sentiment classification using machine learning methods have been widely adopted and proven to provide supreme performance [12][13][14][15][16][17]. Prior research conducted by [10] also showed that machine learning techniques have quite good performance with SVMs tend to do the best.…”
Section: Introductionmentioning
confidence: 99%